2021
DOI: 10.1002/cl2.1185
|View full text |Cite|
|
Sign up to set email alerts
|

Interventions for improving employment outcomes for persons with autism spectrum disorders: A systematic review update

Abstract: Background The incidence of autism spectrum disorders (ASD) is on the rise. Currently, 1 in 59 children are identified with ASD in the United States. ASD refers to a range of neurological disorders that involve some degree of difficulty with communication and interpersonal relationships. The range of the spectrum for autism disorders is wide with those at the higher functioning end often able to lead relatively independent lives and complete academic programs even while demonstrating social awkwardness. Those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 221 publications
(179 reference statements)
0
9
0
Order By: Relevance
“…Within the workplace, the landscape of resources for autistic people in mitigating these difficulties can include job coaches, vocational rehabilitation specialists, occupational therapists or licensed professional counselors (LPC's) [21]. These experts can provide personalized support for autistic individuals across their employment, career pathways, and professional development journeys, but are largely inaccessible and not available at scale for autistic adults [30,91].…”
Section: Related Work 21 Autism In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Within the workplace, the landscape of resources for autistic people in mitigating these difficulties can include job coaches, vocational rehabilitation specialists, occupational therapists or licensed professional counselors (LPC's) [21]. These experts can provide personalized support for autistic individuals across their employment, career pathways, and professional development journeys, but are largely inaccessible and not available at scale for autistic adults [30,91].…”
Section: Related Work 21 Autism In the Workplacementioning
confidence: 99%
“…Given that autistic individuals experience challenges with social interaction in the workplace [5,10,67], researchers have noted the importance of having a champion or advocate who is able to mediate and assist the autistic individual in social or communication challenges at work [59]. Some research has found positive effects that specialized job coaching for autistic job-seekers and counseling with speech and language pathologists (SLPs) can have [21,59,74], but given the challenges and research highlighting the need for more affordable and better support [45,67,74,90], it appears unlikely that autistic workers will access essential resources in most jobs. This underscores the desire for a readily accessible resource that autistic workers can turn to in moments of social difficultya desire which we explore whether large language models (LLMs) can support.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work, however, shows that executive dysfunction may place autistic individuals at a disadvantage, as evidenced by typically longer job search durations for lower quality (e.g., unpaid) employment due to not understanding how to navigate and advance past the interview (Coleman & Adams, 2018), and needing direct assistance from others in finding a job (Wei et al, 2018). Training aimed at improving the social elements (e.g., interviewing) of the job search can help autistic individuals navigate this process (Fong et al, 2021), although we note that this approach does little to enhance understanding of neurodiversity among neurotypical organizational stakeholders with whom an autistic applicant may interact and engage along the way.…”
Section: Navigating the Job Search Processmentioning
confidence: 99%
“…It needs to identify not only the policy implications, but also the uncertainties in the evidence‐base which require further research. Some recent examples are reviews on homelessness (Keenan et al, 2021 ), nutrition (Lassi et al, 2021 ), school‐based interventions for students at risk of academic difficulties (Dietrichson et al, 2021 ), risk factors for radicalization (Wolfowicz et al, 2021 ), using big data for international development (Rathinam et al, 2021 ), employment for persons with autism spectrum disorders (Fong et al, 2021 ), and multisystemic family therapy (Littell et al, 2021 ).…”
mentioning
confidence: 99%